Modelo de gestión para la ejecución presupuestaria óptima en la contratación pública de CNEL EP - Borbor Castro, Silvia Narcisa (2021)
The research work "Management model for optimal budget execution in the public procurement of CNEL EP", defined as general research objective the formulation of a management model based on the Balanced Scorecard for the strategic public company Corporación Nacional de Electricidad CNEL EP Unidad de Negocio Santa Elena so that it can develop the stages of the budget process in an aligned and coherent manner with the institution. Given that there are problems in the execution of the Annual Contracting Plan (PAC), the Annual Operating Plan (POA) and the Budget execution of operating and investment resources, a situation that has a significant impact on meeting the needs of CNEL EP's internal and external customers. A mixed research approach was applied: qualitative and quantitative…………..